2019
DOI: 10.32479/ijeep.8009
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Approach to Sustainable Development: The Case of Energy Efficiency and Solid Waste Management

Abstract: The purpose of this article is to explore the possibilities and develop proposals for the integrated solution of some of the problems of sustainable development related to waste processing and improving the energy efficiency of the economy. This purpose was achieved by solving the following objectives: (1) analysis of the problem of energy efficiency and how to solve it; (2) study of the problem of waste management and approaches to its solution; (3) development of proposals for the implementation of energy-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, its use generates a high amount of waste product. The waste and by-products of the horticultural crops chain are arousing more and more interest; in fact, according to the United Nations [15], the world population is expected to increase from 7.7 billion (2019) to 9.7 billion in 2050, and the annual production of waste, following the current trend, will increase by 70% in the next 40 years [16]. Studies have shown that waste of vegetable processing consists of large amounts of proteins, sugars, and lipids, together with specialized metabolites and, therefore, could be an abundant and cheap source of high value-added products that are potentially useful as health and food products.…”
Section: Introductionmentioning
confidence: 99%
“…However, its use generates a high amount of waste product. The waste and by-products of the horticultural crops chain are arousing more and more interest; in fact, according to the United Nations [15], the world population is expected to increase from 7.7 billion (2019) to 9.7 billion in 2050, and the annual production of waste, following the current trend, will increase by 70% in the next 40 years [16]. Studies have shown that waste of vegetable processing consists of large amounts of proteins, sugars, and lipids, together with specialized metabolites and, therefore, could be an abundant and cheap source of high value-added products that are potentially useful as health and food products.…”
Section: Introductionmentioning
confidence: 99%
“…In the upstream part, in the form of a less than optimal system applied to the final processing (Mulasari, 2016). Most people think that burning waste is part of waste processing (Vertakova, 2019). However, things like that can cause pollution to the environment and interfere with health.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works of researchers are devoted to the issues of increasing the energy efficiency of industrial production in general and chemical-technological systems. The main directions of research in the field of green chemistry and sustainable consumption of energy resources are determined by the work of the following scientists: Chen et al investigated the latest achievements of power engineering in the field of light chemistry [2]; Phan and Luscombe studied recent advances in environmentally friendly, sustainable synthesis of semiconductor polymers [3]; Delgado-Povedano and Luque de Castro evaluated the development of green analytical chemistry [4]; Liu et al substantiated water-soluble, highquality graphene as a green solution for efficient energy storage [5]; Mandal developed the theory of alternative energy sources for sustainable organic synthesis [6]; Wang and Feng deepened the knowledge of advanced materials for green chemistry and renewable energy [7]; Vertakova and Plotnikov proposed new technical energy-saving solutions based on waste processing [8].…”
Section: Introductionmentioning
confidence: 99%